Analisa Deskripsi Minyak dan Gas (Study Kasus Lapangan “X”) - Ramli Nonci (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2020)
Indonesia is one of the countries in the world that have potential of natural resources such as oil and gas. As a resource that plays an important role in the economic life, the use of oil and gas needs to be managed properly. Preparation of the natural resources balance sheet is an important part of the governance of state asset. As of the value of resources must be known so that the government can make the right policies, especially for oil and gas fields that will be terminated. One of the resources of oil and gas that have significant production value and impact to the economy of Indonesia is  the “X” field at East Kalimantan. This study aims to provide an overview of oil and gas processing in the "X" field on valuation date of oil and gas management. Data used in the study came from the results of the discussions, field observations, literature review government policies and company documentation. The analysis conducted in this study is base in description analysis. Based on the results of an analysis that shows the "X" field reduced oil and gas production each year resulted in the realization of "X" field production at the end of 2018  by amounted oil in 183,498 boepd  and  gas in 58,354 MMscfd.